Pengaruh EPS, ROA dan ROE terhadap Harga Saham pada Perusahaan Asuransi yang terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Tiara Ivandri Pratiwi; Muhammad Rivandi (ITScience (Information Technology and Science), 2021)
The stock price is a factor that is very useful for a company and is something that must be kept in mind for an investor. The stock price can arise from the level of supply and demand for a stock. This study aims to determine and analyze the effect of EPS, ROA, and ROE variables partially on stock prices, as well as to determine which variables have the most dominant influence on stock prices in insurance companies. The data processed is secondary data from the annual reports of 11 insurance companies listed on the IDX in 2015-2019 were taken through purposive sampling. The method used in this research is the panel data regression analysis method using Eviews version 8.0. The results of this study indicate that: Earning Per Share has a positive effect on stock prices, Return on Asset and Return on equity has no effect on stock prices